Bioremediation of PCP by Trichoderma and Cunninghamella Strains Isolated from Sawdust - Sing, Ngieng Ngui; Azham, Zulkharnain; Hairul, Azman Roslan; Zani, Assim; Ahmad, Husaini (Scielo, 2014)
Four fungal isolates, SD12, SD14, SD19 and SD20 isolated from the aged sawdust grew on agar plates supplemented with PCP up to a concentration of 100 mg L-1. At high PCP concentration, isolate SD12 showed the highest radial growth rate of 10 mm day-1, followed by SD14 and SD19 both with 4.5 mm day-1 and SD20 with 4.2 mm day-1. Ultrastructural study on the effect of PCP on the PCP tolerant fungi using scanning electron microscope showed that high concentration of PCP caused the collapse of both fungal hyphae and spores. Among the four PCP tolerant fungi examined, isolate SD12 showed the least structural damage at high PCP concentration of 100 mg L-1. This fungal isolate was further characterized and identified as Cunninghamella sp. UMAS SD12. Preliminary PCP biodegradation trial performed in liquid minimal medium supplemented with 20 mg L-1 of PCP using Cunninghamella sp. UMAS SD12 showed that the degradation up to 51.7% of PCP in 15 days under static growth condition.